The correlation between body composition and basic physical fitness in heavyweight university judo athletes and club members - Matsumoto, D.; Tanaka, H.; Nakajima, T.; Iida, E.; Wakayama, H.; Kim, K. H.; Moriwaki, Y. (2001)
Research on the basic physical fitness is important in competitive sports involving winning and losing, especially in Judo. We have employed factor analytic studies to examine basic physical fitness and have developed an 8 factor, 12-item test of basic physical fitness for use with Judo players. But, from the perspective of understanding factor structures, judo is a sport in which weight is a handicap. From the point of view of competition, competitive results have always been correlated strongly with weight. Therefore, there is a need for studies that examine the relationship between weight and body composition. Therefore, in this study, we examined the relationship between performance and not only weight, but also lean body mass (LBM), muscle mass (MM), and total body fat (TBF) (as a negative factor). We also examined differences between selected competitive athletes and club members. One hundred and thirty six judo players from the All Japan University Team Championships and All Japan Elite Judo athletes were separated into 2 groups, one involving competitive athletes (n=40), and the other involving club members (n=96). Body composition was measured using a Tanita TBF-305, which produced data on LBM, MM and TBF. Results: 1) Competitive athletes differed from club members on back strength, vertical jump and push ups with claps. 2) Competitive athletes had significantly higher scores than the club members on LBM and MM; club members had significantly higher scores on the limiting factors of TBF and TBW. From these results, we can begin to understand the importance of body composition in a competitive sport such as Judo, and the importance of reducing body fat, increasing muscle mass, and improving basic physical fitness.